Food Policy Councils: A 20—Year Scoping Review (1999–2019) - Schiff, Rebecca; Levkoe, Charles Z.; Wilkinson, Ashley (Frontiers in Sustainable Food Systems, 2022)
The proliferation of food policy councils (FPCs) in the past two decades has been accompanied by increasing academic interest and a growing number of research studies. Given the rapid interest and growth in the number of FPCs, their expanding geographic distribution, and the research on their activities, there is a need to assess the current state of knowledge on FPCs, gaps in that knowledge, and directions for future research. To address this need, we undertook a scoping review of the scholarly literature published on FPCs over the past two decades. The review identified four main themes in the FPC research - 1) Activities of FPCs; 2) Organizational dimensions; 3) Challenges; and, 4) Facilitators. We also note a significant sub-theme related to equity and diversity, race and class representation in FPCs. These themes frame a growing body of knowledge on FPCs along with key gaps in the current body of literature, which may help to direct research on these organisations for those interested in approaches to food systems change and cross-sectoral collaborative approaches to social-ecological governance.